The Legal Policy for Agricultural Cooperatives as a Pillar of an Empowered National Economy - Purnomo, Wahid Hadi; Santoso, Budi; Prananingtyas, Paramita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Agricultural cooperatives play a strategic role in national economic development, particularly in strengthening food security and empowering farmers. However, their contribution in Indonesia remains low due to weak institutions and historical dependence on state intervention. This article examines the role of legal structure in building integrated and independent agricultural cooperatives, using a normative legal approach and Lawrence M. Friedman's legal system theory, which emphasizes three main elements: structure, substance, and legal culture. Findings indicate that the failure of cooperatives like Agricultural Cooperative and Village Unit Cooperative was triggered by ineffective, bureaucratic, and unresponsive legal structures that failed to adapt to grassroots institutional dynamics. Compared to the success of the National Agricultural Cooperative Federation (NACF) in South Korea, legal structure reforms in Indonesia need to focus on strengthening cooperative institutions, promoting vertical-horizontal integration, and fostering solid inter-agency coordination. The state should act as a facilitator, not a dominator, by providing a legal ecosystem that enables cooperatives to grow as competitive, inclusive, and sustainable people's economic forces.